(3deY GdSMQs - (3CHh YKeGf Hf djhfs; (3GHf GdLdCHj , eMeO Hf CMeO Hf eMeO GdLdGH GdagQj, CHh YHO Gddg,J (B664 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Rjf HGdCOH ef GfJMdg (B[ (3CeGHYO (B] (3aEf GdCOH ef eGJRjf Hg ChdhG GdMSH s
(3BNQgG (B:s
(3hYdefG YdekG jgOi Gdjc hjQZH ef GdKhGH ajeG dOjc jG CQMef GdQGMejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs